ナンキョク コウキアツ カ デ セイセイ シタ ユキ ノ サンソ ドウイタイ ソセイ ダイ1カイ ナンキョク キスイケン シンポジウム - 加藤, 喜久雄; カトウ, キクオ; 樋口, 敬二; ヒグチ, ケイジ; KATO, Kikuo; HIGUCHI, Keiji (1979)
P(論文) 昭和基地の降雪,みずほ高原の飛雪,積雪の酸素同位体組成(δ^<18>O)について考察し,まったくといっていいほど解明されていない南極高気圧下での降雪の生成過程ならびに南極高気庄圏への水蒸気輸送過程について,次のように考えた.南極高気圧下では上層逆転層付近に相対湿度100%のところがあり,そこで混合または放射冷却により等圧冷却過程で降雪が生成している.南極高気圧圏へは,海から蒸発した水蒸気は沿岸低気圧地域の上空を通って供給され,南極高気圧圏内て下降し,カタバティック風により沿岸地域へ運ばれる.下降流により沈降性上層逆転層が生成される.晴天が多いため地表気温は低くなるので,氷床上では等圧冷却過程で生成した降雪から氷床上の雪への水蒸気の移動が起こる.その結果として積雪の霜さらめ化と上向きの結晶生長ならびに表面積雪層における雪のδ^<18>値が深くなるにつれて小さくなるというδ^<18>0値の垂直分布がひきおこされる. In order to investigate the formation process of snow under an Antarctic anticyclone and the transportation process of water vapor into the anticyclone, the oxygen isotopic composition of fallen snow at Syowa Station and drifting snow and firn in Mlzuho Plateau was determined. Fallen snow at Syowa Station is formed by the isobaric cooling process from a cloud layer under the upper inversion. Water vapor is transported to the Antarctic anticyclone and subsides in it. Snow is formed by the isobaric cooling process under the subsidence inversion. The surface air temperature is much lower than the temperature of formation of snow. Therefore, on ice sheet, water vapor moves from fallen snow to surface snow. The systematic decrease of oxygen isotopic compostion of snow with depth is formed in the snow cover with well developed depth-hoar of upward crystal growth under the influence of an Antarctic anticyclone, whereas the systematic increase is formed in that with depth-hoar of downward crystal growth under the influence of a circumpolar cyclone. departmental bulletin paper